Crop performance and nitrogen use-efficiency in maize under conservation agriculture coupled with sub-surface drip fertigation - PATRA, KIRANMOY; PARIHAR, C M; NAYAK, H S; RANA, BISWAJIT; SINGH, V K; KRISHNAN, P; PANDEY, RENU; MANDAL, B N; RATHI, N; MEENA, B R; SINGH, L K; SIDHU, H S; et al. (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted in maize under medium-term conservation agriculture (CA) based maizewheat system at BISA-CIMMYT, Ladhowal, Punjab during kharif 2019 to assess the effect of CA+ practices (CA with sub-surface drip irrigation) with variable N doses on maize. The CA+ treatments were residue retained (WR) permanent bed (PB) with sub-surface drip fertigation (PB-SSD): without N (N0), 120 kg N/ha,150 kg N/ha applied in 4-equal (Eq) and differential splits (Df); CA alone treatment includ PB furrow irrigation with 120 kg N/ha (PBWRFurrow- N120); conventional tillage (CT) involved furrow irrigation with 120 kg N/ha (CTWOR-Furrow-N120) and other treatments were residue removed (WOR) PB: PBWOR-without N (N0), with 120 kg N/ha, and 150 kg N/ha applied in four Eq-splits and Df-splits. The findings of the present experiment showed that the numerical value of yield attributing characters were higher under CA+ plots as compared to CA alone (PBWR-Furrow-N120) and CT (CTWOR-Furrow-N120). Biological yield of maize was significantly higher in all CA+ plots as compared to CA alone and CT plots. Highest biological yield was recorded under PBWR-SSD-N150 Df (23.45 t/ha). Highest no. of cobs (72800/ha), no. of grains/cob (605) and cob length (22.61cm) along with dry matter resulted highest biological yield in PBWR-SSD-N150 plots. The grain N content remained statistically similar across all the N management plots, but in case of total N uptake, PBWR-SSD-N150 Df (CA+) plots dominated due to higher biomass. Besides, CA+ based PBWR-SSD-N120 (average of Df and Eq) registered 23-24% higher total N uptake than CA alone (PBWRFurrow- N120) and conventional (CTWOR-Furrow-N120) plots. Improved agronomic N use-efficiency was also recorded under CA+ plots as compared to CA alone (36.4 kg/kg N) and CT (36.7 kg/kg N) plots.